A neglected problem ın caregıvers of cancer patıents: Supportıve care needs - Çelik, Ayşegül; Temeltaş, Gizem (Health & Research Journal, 2024)
Background: Supportive care approaches are critical in meeting the needs of cancer patients and their families when they are diagnosed, during cancer treatment, and after therapy. The aim of this study was to determine the supportive care needs of cancer caregivers. Methods: The study was descriptive and quantitative. Data was collected online between December 2021 and February 2022. The study’s sample included 170 people aged 18 years up who had been responsible for the care of cancer patients for at least three months. “Partners and Caregivers Descriptive Information Form” and “Supportive Care Needs Survey Partners and Caregivers of Patients Diagnosed with Cancer” were used to collect data. Results: According to the study, 81.2% of caregivers were female, 52.9% had a bachelor’s degree, 74.1% were married, and 61.2% had a job. Additionally, 26.5% of individuals provided care to lung cancer patients, 64.1% lived with the patient, and 26.5% dedicated 7-12 hours each day to the provision of care. The most common supportive care needs of caregivers were psychological and emotional support (87.0%). Educational level, perceived income status, relationship with the patient and daily caregiving duration were determined as caregiver characteristics that affect supportive care needs (p<0.05). Conclusion As a result of the research, it was determined that the partners and caregivers who care for cancer patients have a high level of supportive care needs. Psychological and emotional support was the most frequently reported need for supportive care by cancer patients caregivers in Turkish society.